Adverse vacuolation in multiple tissues in cynomolgus monkeys following repeat-dose administration of a PEGylated protein. (15th December 2019) - Fletcher, Anthony M.; Tellier, Pierre; Douville, Julie; Mansell, Peter; Graziano, Michael J.; Mangipudy, Raja S.; Brodie, Thomas A.; Achanzar, William E.
Highlights: PEG related vacuolation was observed in macrophages and epithelia in multiple tissues. Vacuolation was considered adverse in choroid plexus, pituitary, kidney, and eye. Adversity was due to structural alterations and potential for tissue dysfunction. Positive PEG immunohistochemistry was detected in choroid plexus and kidney. Abstract: PEGylation is considered a safe mechanism to enhance the pharmacokinetics (PK) and pharmacodynamics (PD) of biotherapeutics. Previous studies using PEGylation as a PK enhancement tool have reported benign PEG-related vacuolation in multiple tissues. This paper establishes a threshold for PEG burden beyond which there are alterations in tissue architecture that could potentially lead to dysfunction. As part of the nonclinical safety assessment of Compound A, a 12 kDa protein conjugated to a 40 kDa branched PEG molecule, monkeys were dosed subcutaneously twice weekly for 3 months at protein doses resulting in weekly PEG doses of 8, 24, 120, or 160 mg/kg. Consistent with previous reports with PEGylated biomolecules, Compound A administration resulted in intracellular vacuoles attributed to the PEG moiety in macrophages in numerous tissues and epithelial cells in the choroid plexus and kidney. Vacuolation occurred at all doses with dose-dependent severity and no evidence of recovery up to 2 months after dosing cessation. The vacuolation was considered nonadverse at PEG doses ≤120 mg/kg/week. However, at 160 mg/kg/week PEG, the vacuolation in choroid plexus, pituitary gland, kidney, and choroid of the eye was considered adverse due to significant alterations of tissue architecture that raised concern for the possibility of compromised tissue function. To our knowledge, this is the first report of potentially adverse cellular consequences of PEG accumulation in tissues other than kidney. Furthermore, the lack of reversibility of vacuolation coupled with the lack of a biomarker for intracellular PEG accumulation highlights a potential risk that should be weighed against the benefits of PK/PD enhancement for long-term administration of PEGylated compounds at high doses.